Comparing measures of competitiveness - Klaus Frohberg; Monika Hartmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1997)
In their Europe Agreements with the EU, the Central and Eastern European countries stated their intention of joining the Union. To ease the process of accession these countries must adjust their economies already prior to becoming an EU-member. Agriculture requires special attention, because it still represents a large share of the total economy in these countries. A better understanding of the competitiveness of agricultural products at domestic and EU markets is essential for providing the necessary economic framework to make the process of joining the EU as smooth as possible.Competitiveness can be analyzed at various levels of the economy: at the enterprise level, the sector level, or the level of the entire economy. Several measures exist for each of these levels. This paper focuses on those used for sector analysis. Since the measures commonly employed for this purpose do not deliver the same results, a better understanding of the underlying causes is necessary. This paper discusses the differences between the various indicators. It identifies the factors leading to disagreement in the results obtained. – – In den Assoziierungsabkommen mit der EU haben die mittel- und osteuropäischen Länder ihr Interesse an einer EU-Mitgliedschaft bekundet. Um den Integrationsprozeß zu erleichtern, müssen diese Länder ihre Wirtschaft anpassen. Die Landwirtschaft verdient dabei besondere Aufmerksamkeit, da sie einen nicht geringen Anteil an der gesamten wirtschaftlichen Leistung erbringt. Kenntnis über die Wettbewerbsfähigkeit landwirtschaftlicher Produkte dieser Länder ermöglicht es, die ökonomischen Voraussetzungen für einen möglichst reibungslosen Übergang in die EU zu erreichen. Wettbewerbsfähigkeit läßt sich auf verschiedenen Stufen der Wirtschaft messen; auf betrieblicher Ebene, für einen Sektor oder für die gesamte Volkswirtschaft. Auf jeder dieser Stufen gibt es verschiedene Indikatoren. In diesem Diskussionspapier werden solche Indikatoren beschrieben, die zur Messung der Wettbewerbsfähigkeit auf sektoraler Ebene herangezogen werden können. Da sich die Meßzahlen unterscheiden und auch nicht zwingend die gleichen Ergebnisse liefern, ist die Kenntnis der Gründe für diese Abweichungen in den Ergebnissen sehr wichtig. Dieses Papier untersucht und beschreibt die Faktoren, die zu derartigen Unterschieden führen.
urn:nbn:de:gbv:3:2-22616
Keywords: 330; Landwirtschaft; Internationaler Wettbewerb; Komparativer Kostenvorteil; Index; Theorie